RORB and RORC associate with human islet dysfunction and inhibit insulin secretion in INS-1 cells. Issue 1 (2nd January 2019) - Taneera, Jalal; Mohammed, Abdul Khader; Dhaiban, Sarah; Hamad, Mawieh; Prasad, Rashmi B.; Sulaiman, Nabil; Salehi, Albert
ABSTRACT: Little is known about the expression and function of Retinoic acid-related orphan receptors ( RORA, B, and C ) in pancreatic β cells. Here in, we utilized cDNA microarray and RNA sequencing approaches to investigate the expression pattern of ROR receptors in normal and diabetic human pancreatic islets. Possible correlations between RORs expression and HbA1c levels as well as insulin secretory capacity in isolated human islets were evaluated. The impact of RORB and RORC expression on insulin secretion in INS-1 (832/13) cells was validated as well. While RORA was the highest expressed gene among the three RORs in human islet cells, RORC was the highest expressed in INS-1 cells (832/13) and while RORB was the lowest expressed gene in human islet cells, RORA was the highest expressed in INS-1 cells (832/13). The expression of RORB and RORC was significantly lower in diabetic/hyperglycemic donors as compared with non-diabetic counterparts. Furthermore, while the expression of RORB correlated positively with insulin secretion and negatively with HbA1c, that of RORC correlated negatively with HbA1c . The expression pattern of RORA did not correlate with either of the two parameters. siRNA silencing of RORB or RORC in INS-1 (832/13) cells resulted in a significant downregulation of insulin mRNA expression and insulin secretion. These findings suggest that RORB and RORC are part of the molecular cascade that regulates insulin secretion in pancreatic β cells; and insight that provides for further work on the potential therapeutic utility of RORB and RORC genes in β cell dysfunction in type 2 diabetes.